2006
DOI: 10.1186/cc5068
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is increased in critically ill patients according to antioxidant vitamins intake, independent of severity: a cohort study

Abstract: Introduction Critically ill patients suffer from oxidative stress caused by reactive oxygen species (ROS) and reactive nitrogen species (RNS). Although ROS/RNS are constantly produced under normal circumstances, critical illness can drastically increase their production. These patients have reduced plasma and intracellular levels of antioxidants and free electron scavengers or cofactors, and decreased activity of the enzymatic system involved in ROS detoxification. The prooxidant/antioxidant balance is of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 38 publications
1
28
0
2
Order By: Relevance
“…The growth of oxidative stress index is a concomitant phenomenon of a decrease in the conversion of thyroxine (T 4 ) to triiodothyronine (T 3 ), in particular with nonthyroid illness syndrome (NTIS). This suggests that oxidative stress in this case is not only a sign of the adaptation process but also connected with the state of hypothyroidism (Abilés et al, 2006;Mancini et al, 2016).…”
Section: Discussionmentioning
confidence: 69%
“…The growth of oxidative stress index is a concomitant phenomenon of a decrease in the conversion of thyroxine (T 4 ) to triiodothyronine (T 3 ), in particular with nonthyroid illness syndrome (NTIS). This suggests that oxidative stress in this case is not only a sign of the adaptation process but also connected with the state of hypothyroidism (Abilés et al, 2006;Mancini et al, 2016).…”
Section: Discussionmentioning
confidence: 69%
“…Even if this replenishment concerns relatively short periods, toxicity [109, 110] is to be kept in mind and appropriate measures should be applied in order to avoid it. In general, the substitution of more than 66% of the recommended daily allowance of vitamins A, C, and E has been shown to improve antioxidant capacity [112]. REDOXS (Reducing Deaths due to Oxidative Stress) study is a blinded randomized trial in 1223 critically ill patients that failed in meeting its original rationale and concluded that the administration of antioxidants and glutamine increased mortality [113].…”
Section: Introductionmentioning
confidence: 99%
“…New findings from this study include the following: 1) OZ rats have increased tubular injury as compared to LZ rats following trauma; 2) OZ rats have increased renal ROS production following trauma as compared to LZ rats, as well as impaired baseline and posttrauma Increased renal oxidative stress in OZ rats following trauma. Studies have shown that ROS are acutely upregulated in the setting of critical illness, and can have adverse 238 effects on a number of organs(1,18,31,52). However, little work has been done comparing the obese and lean acute oxidative stress responses to critical illness.…”
mentioning
confidence: 99%